Structure of sulfamidase provides insight into the molecular pathology of mucopolysaccharidosis IIIA. (1st May 2014) - Sidhu, Navdeep S.; Schreiber, Kathrin; Pröpper, Kevin; Becker, Stefan; Usón, Isabel; Sheldrick, George M.; Gärtner, Jutta; Krätzner, Ralph; Steinfeld, Robert
<x xml:space="preserve">Abstract</x> Mucopolysaccharidosis type IIIA (Sanfilippo A syndrome), a fatal childhood‐onset neurodegenerative disease with mild facial, visceral and skeletal abnormalities, is caused by an inherited deficiency of the enzyme N‐sulfoglucosamine sulfohydrolase (SGSH; sulfamidase). More than 100 mutations in the SGSH gene have been found to reduce or eliminate its enzymatic activity. However, the molecular understanding of the effect of these mutations has been confined by a lack of structural data for this enzyme. Here, the crystal structure of glycosylated SGSH is presented at 2 Å resolution. Despite the low sequence identity between this unique N‐sulfatase and the group of O‐sulfatases, they share a similar overall fold and active‐site architecture, including a catalytic formylglycine, a divalent metal‐binding site and a sulfate‐binding site. However, a highly conserved lysine in O‐sulfatases is replaced in SGSH by an arginine (Arg282) that is positioned to bind the N‐linked sulfate substrate. The structure also provides insight into the diverse effects of pathogenic mutations on SGSH function in mucopolysaccharidosis type IIIA and convincing evidence for the molecular consequences of many missense mutations. Further, the molecular characterization of SGSH mutations will lay the groundwork for the development of structure‐based drug design for this devastating neurodegenerative disorder.